1991
DOI: 10.1111/j.1528-1157.1991.tb04668.x
|View full text |Cite
|
Sign up to set email alerts
|

Felbamate: A Clinical Trial for Complex Partial Seizures

Abstract: We performed a randomized, double-blind, three-period cross-over study of felbamate (FBM, 2-phenyl-1,3-propanediol dicarbamate: Carter-Wallace 554) in patients with complex partial seizures. Patients continued carbamazepine (CBZ) throughout the study and were observed in the hospital for the entire trial period. The entry criteria required at least six seizures in a 3-week baseline period (and no more than 1 week with a single seizure) with CBZ alone. Thirty subjects were randomized. Two left the study after r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(44 citation statements)
references
References 8 publications
1
42
1
Order By: Relevance
“…6). In view of the 50 to 300 M (mean, ϳ150 M) therapeutic concentrations of FBM in plasma or brain (Leppik et al, 1991;Theodore et al, 1991;The Felbamate Study Group in LennoxGastaut Syndrome, 1993;Adusumalli et al, 1994), a K f,c of 200 M would imply that a significant proportion (on average, nearly half) of the NMDA channel is already bound and modified by FBM when the neuron is at rest. This is in sharp contrast to the cases of other major anticonvulsants phenytoin, carbamazepine, and lamotrigine, which are Na ϩ -channel inhibitors and share a common anticonvulsant binding site in the channel (Kuo, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). In view of the 50 to 300 M (mean, ϳ150 M) therapeutic concentrations of FBM in plasma or brain (Leppik et al, 1991;Theodore et al, 1991;The Felbamate Study Group in LennoxGastaut Syndrome, 1993;Adusumalli et al, 1994), a K f,c of 200 M would imply that a significant proportion (on average, nearly half) of the NMDA channel is already bound and modified by FBM when the neuron is at rest. This is in sharp contrast to the cases of other major anticonvulsants phenytoin, carbamazepine, and lamotrigine, which are Na ϩ -channel inhibitors and share a common anticonvulsant binding site in the channel (Kuo, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, very low concentrations of FBM inhibited up to ϳ40% of high-voltage-activated Ca 2ϩ currents in rat cortical neurons (IC 50 ϭ 504 nM) (Stefani et al, 1996). In this regard, it should be noted that the clinical effect of FBM usually requires a therapeutic dosage of 2400 to 3600 mg/day, which results in plasma or brain FBM concentrations of 50 to 300 M (mean, ϳ150 M) (Leppik et al, 1991;Theodore et al, 1991;The Felbamate Study Group in Lennox-Gastaut Syndrome, 1993;Adusumalli et al, 1994). In addition, reduction of seizure frequency is generally well correlated with FBM concentration in this range (The Felbamate Study Group in Lennox-Gastaut Syndrome, 1993).…”
mentioning
confidence: 99%
“…1 Felbamate is generally well tolerated, with the most common adverse effects being insomnia, dizziness, fatigue, decreased appetite, weight loss, nausea, ataxia, and lethargy. [2][3][4][5] In 110,000 patients, there were 10 cases of fatal aplastic anemia and 14 cases of fatal hepatic failure. The labeling was changed to advise that it be utilized in a limited subset of patients along with bi-weekly blood monitoring.…”
Section: Felbamatementioning
confidence: 99%
“…Though its exact mechanism of action is undefined, predinical evaluations have indicated that felbamate appears to increase seizure threshold and prevent seizure spread (65). In controlled clinical studies, felbamate has demonstrated efficacy as adjunctive therapy in the treatment of partial and generalired seizures in adults (66)(67)(68). In addition, felbamate as monotherapy was superior to a nontherapeutic dose of valproic acid (69,70).…”
Section: New Antiepileptic Medicationsmentioning
confidence: 99%